Hypotheses on Biology and Co-existence of Woody Plants in a Forest Ecosystem - Maiti, Ratikanta; Rodriguez, Humberto Gonzalez (International Journal of Bio-resource and Stress Management, 2023)
In a forest ecosystem woody plants are predominantand grow in a harmony with other species in sharing and capturing solar radiation and absorbing nutrients and water from different soil profiles with their rootsystems. There exist large variations in crown architecture, branching pattern,leaf canopy with simple to compound leaves. Top crown leaves function as solar panel in capturing the solar radiation. In a forest ecosystem varied trees and shrubs exist in different strata. Each strata comprises of trees and shrubs of definite heights, those that have faster growth rate are able to capture the solar radiation in a very efficient manner and occupy the top layer of the strata. As the light is absorbed while passing through the canopy a large portion of it is rich in the far red wavelength of light. Mutual shading by the top most leaves occur and the shade loving plants are mostly seen as the bottom ground layers. The arrangement of trees and shrubs at different heights in this ecosystem enables them to utilize the solar radiation more effectively. Further most of these also exhibit stratification of the root structure also. Some will be possessing deep roots and others superficial roots, where roots are confined to over a few centimeters deep in the soil. This is also an adaptation enabling the plants to overcome the competitive effects among themselves for nutrients, water etc. .....